Statistics for Social Sciences: with Spss Application - Hari Shankar Asthana (Prentice-Hall of India, 2007)
Designed as a text for the undergraduate and postgraduate students of psychology, education, sociology, demography and economics, this comprehensive book explains the theoretical and computational aspects of statistics. Since the students of social sciences often find it difficult to comprehend easily the statistical techniques due to complex mathematical steps involved, this book explains the concepts as well as steps in a simple and clear manner.The text provides solutions to basic concepts and problems using a number of illustrations. In addition, it demonstrates the simplest way of using SPSS software for statistical analysis.SPSS screen images are used to make the ideas clearer for the readers. This is preceded by theoretical details and solved examples so that even readers having minimal knowledge of computer can use SPSS easily and comprehend the complex intermediate steps involved in statistical analysis.Besides the undergraduate and postgraduate students of social sciences, researchers in the field of social sciences should find this book immensely useful.This title demonstrates the simplest way of using SPSS for statistical analysis. It provides solved examples throughout the text in ascending order of complexity. It gives chapter-end exercises and key terms for better grasp of the topics covered.